Exploration of defensive protein Amylase Trypsin Inhibitors from wheat: A novel approach for crop protection: Amylase Trypsin inhibitors - Choudhary, Sapna; Gaur, Rajarshi Kumar (Journal of Cereal Research, 2023)
Insect pests are highly dependent on starch-rich cereals and cause severe damage to the cereal grain and nutrient yield. Amylase trypsin inhibitor protein degrades the digestive enzyme alpha-amylase which plays a key role in carbohydrate metabolism as well as the growth and development of insects. These inhibitor proteins are mainly found in cereal crops like wheat, maize, and barley which are rich sources of starch. Due to the defensive mechanism against pests, Amylase trypsin inhibitor protein is a prominent candidate for pest management in cereal crops. It could be used in marker-assisted plant breeding and genome mapping. This review contains information on amylase trypsin inhibitor proteins their characterization, mechanism, purification, and various analyses. Amylase trypsin inhibitor proteins prevent various diseases such as diabetes but also cause wheat allergy, baker’s asthma, and food allergies. The reviewed information allows further strategies and information to control pests from cereal crops as a natural defense and reduce human allergies.